2019
DOI: 10.7567/1347-4065/ab0491
|View full text |Cite
|
Sign up to set email alerts
|

Tensile mechanical properties of sintered porous silver films and their dependence on porosity

Abstract: This paper investigates the porosity-dependent tensile mechanical properties of porous silver films that are 8-10 μm thick. The silver films are fabricated with a pressure press; the use of different pressures changes the porosity (p) in the range of 5% to 25%. p is determined using scanning electron microscopy cross-sectional images of the films. Stress-strain (S-S) curves are obtained by tensile tests performed on the porous and bulk silver films. The conventional ductile plateau disappears from the porous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The dwell time was set to 3 min. After 3000 cycles passed, the reliability was found to increase with decreasing s-Ag p. The results indicated that lower p of s-Ag had a good influence on TST reliability, which had good agreement with our mechanical testing results of s-Ag [27].…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…The dwell time was set to 3 min. After 3000 cycles passed, the reliability was found to increase with decreasing s-Ag p. The results indicated that lower p of s-Ag had a good influence on TST reliability, which had good agreement with our mechanical testing results of s-Ag [27].…”
Section: Introductionsupporting
confidence: 85%
“…One of the difficulties is the s-Ag material characteristic that inevitably includes micropores as a stress concentration area. As for the essential steps for understanding the degradation mechanism during TST, many researchers have investigated micropores' dependence on s-Ag tensile mechanical properties [20][21][22][23][24][25][26][27][28]. Particularly, authors focused on micropores' dependence on its tensile mechanical properties by applying changed process pressure from 5 to 60 MPa with nanosized silver paste (NP) as a function of the s-Ag porosity rate (p) at room temperature [24].…”
Section: Introductionmentioning
confidence: 99%
“…The s-Ag of p was calculated based on cross sectional SEM images because the method could give enough information about microstructure of s-Ag without any troublesome [ 9 , 11 , 14 ]. Figure 3 shows representative cross-sectional SEM image of s-Ag along with the binary image after filtering.…”
Section: Resultsmentioning
confidence: 99%
“…However, by virtue of including many pores in s-Ag, it is very difficult to finely estimate the mechanical behaviors. To date, many researchers have tried to examine how porous affect the mechanical properties of s-Ag [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] by means of indentation test [ 20 ] and bending test [ 21 , 22 , 23 ]. Although the tensile test is one of the most basic mechanical property evaluation tests, these alternative mechanical tests have been utilized for the evaluation due to its technical simplicities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation